Morality and Values in Sports Among Young Athletes: The Role of Sport Type and Parenting Styles – A Pilot Study - Yaffe, Yosi; Levental, Orr; Arey, Dalit Lev; Lev, Assaf (Frontiers in Psychology, 2021)
Given the great importance of morality and values in modern sports, especially among young athletes, in this pilot study we sought to broaden the exploration of the factors that may play role in these contexts, which have not been widely researched to date. Accordingly, the study tested the relationships between sport type (team or individual) and parenting styles (authoritative vs. non-authoritative), and moral decision-making in sport and sport values amongst 110 adolescent athletes whose age ranges from 11 to 22 (M = 16.04, SD = 2.86). The findings indicated that participants with authoritative parents, as compared to those with non-authoritative parents are significantly less accepting of cheating in sport, while they also tend more to keep winning in proportion and hold significantly stronger moral values toward sports. Moreover, participants whose main sport is a team sport type tend to accept more cheating and gamesmanship than participants whose main sport is an individualistic sport type. While no differences were recorded between these groups in moral values, team athletes tend to value status in sport more than individual athletes, while the latter tend to value competence regarding their sport. The implications of the findings are discussed in light of no interaction between the effects of parenting styles and sport type on moral and sport values.